Preparation method of Zr-based amorphous alloy film and film
By preparing the ZR -based amorphous alloy film on the surface of the 304 stainless steel to control the NB content, the problem of insufficient corrosion resistance of traditional alloy materials in the marine environment has been solved, and the significant corrosion resistance and cost reduction have been achieved.
Patent Information
- Application Number
- CN202411551005.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional metal alloy materials are difficult to meet the corrosion resistance requirements in harsh environments in marine environments, and the prior art is difficult to effectively improve their corrosion resistance.
Magnetic sputtering technology is prepared to prepare the ZR infrastructure thin film on the surface of 304 stainless steel to control the NB content of the amorphous thin film to improve its corrosion resistance.
A significant improvement of the corrosion resistance of the ZR -based non -crystal alloy film in the marine environment, prolonged its service life, and reduced preparation costs.
Smart Images

Figure CN119372610A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of alloy material preparation, and in particular to a method for preparing a Zr-based amorphous alloy film. Background Art
[0002] Amorphous alloys refer to alloys with metal elements as the main components, which are arranged topologically in three-dimensional space and remain relatively stable in a liquid-like chaotic state within a certain temperature range. Since amorphous alloys do not have defects such as grain boundaries and dislocations in their crystallographic structure, amorphous alloy materials exhibit excellent physical and chemical properties such as high hardness and corrosion resistance.
[0003] Among many amorphous systems, Zr-based amorphous alloys have strong glass-forming ability and are one of the earliest amorphous alloys developed. The study of Zr-based amorphous alloys has always been a hot topic in the field of amorphous alloys, especially its corrosion resistance and mechanism. Some materials need to be used in complex and severe environments (such as marine environments) for a long time, such as seawater desalination equipment, offshore oil and gas field equipment, ocean-going giant ships, etc. Traditional metal alloy materials (such as stainless steel) can no longer meet the requirements of industrial production in these harsh environments. It is particularly important to study materials with excellent corrosion resistance or to effectively protect materials in corrosive environments. Summary of the invention
[0004] In view of the above problems, the present application provides a method for preparing a Zr-based amorphous alloy film, which prepares a Zr-based amorphous alloy film on the surface of 304 stainless steel and performs surface modification on the film to improve the corrosion resistance of the alloy material in a marine environment.
[0005] Specifically, this application is obtained through the following technical solutions:
[0006] First, the present application provides a method for preparing a Zr-based amorphous alloy thin film (Thin Film Metallic Glass, TFMG), that is, 75 Cu 25 The Zr-based amorphous alloy film is prepared on the surface of 304 stainless steel under specific temperature, atmosphere, bias voltage, power and time conditions by magnetron sputtering with target material Nb through PVD. The specific steps are as follows:
[0007] 3) After cleaning the substrate 304ss (304 stainless steel), place it on the upper end of the vacuum chamber with a high-temperature tape, and fix the target Zr with a nut. 75 Cu 25 and target material Nb are fixed directly below the substrate, and the chamber is evacuated;
[0008] Before using the two target materials, the surface of the target materials was polished with sandpaper (800, 1500 mesh) with varying roughness from coarse to fine to remove the oxides on the surface.
[0009] 4) Sputtered thin film
[0010] Zr 75 Cu 25 The sputtering power of the target material is set to 150W, the sputtering power of the Nb target material is set to 18-30W, and the sputtering time is 50 minutes; to gradually control the Nb content of the amorphous film.
[0011] In this step, the Nb content of the amorphous film is controlled by adjusting the sputtering power of the Nb target. For example, in the embodiment, the sputtering power of the Nb target is adjusted to 18W, 24W, and 30W in sequence to obtain films with different Nb contents.
[0012] 3) After the sputtering is completed, the baffle, sputtering source, vacuum chamber heating device, and airflow are closed in sequence. After the air pressure in the vacuum chamber returns to atmospheric pressure, the chamber door is opened to take out the sample, and the above-mentioned Zr-based amorphous alloy film is formed on the surface of the substrate 304 stainless steel.
[0013] Furthermore, the above cleaning refers to: carefully polishing the substrate coating surface with sandpaper of roughness from coarse to fine (200, 400, 800, 1500, 2000 mesh) in sequence, and polishing the substrate coating surface into a smooth mirror surface with a metallographic polishing machine and polishing paste, and then using anhydrous ethanol to ultrasonically clean the substrate surface for 20 minutes at room temperature; finally, ultrasonically clean the substrate with deionized water for 20 minutes at room temperature and blow dry the substrate with a hair dryer for use.
[0014] Furthermore, the above step 1) vacuuming refers to using a mechanical pump to pump the pressure in the vacuum chamber to below 10Pa (i.e., low vacuum), and then turning on the molecular pump to continue vacuuming to below 6×10-4Pa (i.e., high vacuum) to reduce the influence of impurity elements in the air on the experimental results.
[0015] Furthermore, before the above step 2) sputtering the film, the bias power supply in the equipment was turned on at -800 V, the Ar gas flow rate was set to 100 sccm, and the surface of the substrate was bombarded and cleaned for 15 minutes, so that the surface of the 304 stainless steel substrate obtained a relatively clean surface after repeated particle impact. ; Then, the temperature of the vacuum chamber is raised to 150°C, the Ar gas flow rate is set to 50 sccm, the sputtering bias is -40V, and a DC power supply is used for pre-sputtering for 10 minutes to remove oxides or other impurities on the target surface. After the sputtering voltage stabilizes (this indicates that the impurities on the target surface have been cleaned up), the baffle is opened for magnetron sputtering.
[0016] Secondly, the present application also provides a Zr-based amorphous alloy film prepared according to the above method.
[0017] Third, the present application also provides a Zr-based amorphous alloy thin film material, the chemical formula of which is Zr 75.2 Cu 17.7 Nb 7.7 、Zr 72.3 Cu 18.2 Nb 9.5 and Zr 68.6 Cu 20 Nb 11.4 .
[0018] The present invention prepares ZrCuNb amorphous films with different Nb contents by magnetron sputtering, and evaluates their corrosion resistance. It is found that with the significant expansion of the passivation zone, the corrosion resistance is improved. In particular, when the Nb content is 9.5at.%, the ZrCuNb film has the best corrosion resistance. The examples of the present application verify that the ZrCuNb TFMG / 304ss composite material has a significantly higher cumulative corrosion potential than the uncoated 304ss substrate, which is the driving force for the preferential corrosion of the film layer to protect the 304ss substrate. At the same time, the superior resistance of the amorphous composite material to pitting corrosion is established by the difference in self-corrosion current density of about one order of magnitude. The EIS results show that the capacitance semicircle diameter associated with the charge transfer resistance is larger, indicating a slower corrosion rate and better corrosion resistance, which is consistent with the observed potentiodynamic polarization performance.
[0019] Compared with the prior art, the present application adds Nb element to the ZrCuNb amorphous film. Nb can generate Nb2O5 in electrochemical experiments and inhibit the oxidation of Zr, Cu and other elements. The metal oxidation products are enriched on the surface of the film. The addition of Nb can reduce the corrosion current of the film, increase the corrosion potential, slow down the corrosion rate of the film, reduce the corrosion tendency of the film, and ultimately improve the corrosion resistance of the ZrCuNb TFMG / 304ss composite material.
[0020] The raw materials of the present invention are easy to obtain, and the preparation method is simple and easy, which greatly reduces the preparation cost of the alloy, greatly improves the corrosion resistance of 304ss, and inhibits the occurrence of pitting corrosion of 304ss by adding the Nb element. The alloy system can be widely used in extreme environments such as the ocean, which greatly broadens the industrial application scenarios of amorphous alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings constitute a part of the present application and are used to provide a further understanding of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the accompanying drawings:
[0022] Figure 1 1 is the polarization curve of the Zr-based thin film with different Nb contents in Example 1 of the present invention in a 3.5wt.% sodium chloride solution;
[0023] Figure 2 is Zr in Example 1 of the present invention 72.2 Cu 18.3 Nb 9.5 EDS image of amorphous film;
[0024] Figure 3 is Zr in Example 1 of the present invention 72.2 Cu 18.3 Nb 9.5 GIXRD pattern of amorphous film;
[0025] Figure 4 The 304ss substrate in Example 1 of the present invention, ZrCu and Zr 72.2 Cu 18.3 Nb 9.5 Potentiodynamic polarization curves of amorphous films.
[0026] Figure 5 This is a scanning electron microscope image of a 3.5 wt. % sodium chloride solution subjected to potentiodynamic polarization at room temperature in Example 1 of the present invention;
[0027] Among them, (a) is an uncoated 304ss substrate, (b) is a Zr 72.2 Cu 18.3 Nb 9.5 Amorphous film. DETAILED DESCRIPTION
[0028] Zr used in the examples 75 Cu 25 The Nb and Nb targets were purchased from Nanchang Guocai Technology Co., Ltd. The target diameter is 50 mm, the thickness is 4 mm, and the target purity is 99.9%.
[0029] 304 stainless steel plates were purchased from the Scientific Metal Research Institute;
[0030] High temperature tape was purchased from Dongwan Jinbeiyu Adhesive Tape Co., Ltd.;
[0031] The vacuum coating machine was purchased from Beijing Techno Corporation, model JCP-650M6.
[0032] Unless otherwise specified, the raw materials and equipment used in the examples are commercially available.
[0033] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0034] Example 1 Preparation (Zr 75 Cu 25 )Nb x Amorphous film
[0035] A method for preparing an amorphous alloy thin film comprises the following steps:
[0036] Step 1: Use laser to cut 304 stainless steel plate (5 mm thick) into 10 mm × 10 mm size, use sandpaper with roughness from coarse to fine (200, 400, 800, 1500, 2000 mesh) to carefully polish the coated surface of 304 stainless steel substrate, and use metallographic polishing machine with polishing paste to polish the coated surface of substrate into a smooth mirror surface, and then use anhydrous ethanol to ultrasonically clean the substrate surface for 20 min at room temperature, with an ultrasonic power of 10 W; finally, use deionized water to ultrasonically clean for 20 min at room temperature, and use a hair dryer to blow dry the substrate to obtain a cleaned stainless steel substrate for standby use.
[0037] Sandpapers with different roughness from coarse to fine (800 and 1500 mesh) were used to rub Zr 75 Cu 25 Carefully polish the surface of the Nb target to remove the surface oxide and set aside.
[0038] Step 2: Place the cleaned substrate 304ss on the upper end of the vacuum chamber of the vacuum coating machine through high-temperature tape, and fix the target Zr with a nut. 75 Cu 25 and target material Nb are fixed directly below the substrate respectively.
[0039] Step 3: Use a mechanical pump to pump the pressure in the vacuum chamber to below 10Pa (i.e., low vacuum), and then turn on the molecular pump to continue pumping the pressure to below 6×10-4Pa (i.e., high vacuum) to reduce the impact of impurity elements in the air on the experimental results.
[0040] Step 4: Before sputtering the film, turn on the bias power supply in the equipment at -800V, set the Ar gas flow rate to 100sccm, and bombard and clean the substrate surface for 15 minutes, so that the surface of the 304 stainless steel substrate obtains a relatively clean surface after repeated particle impact. Then, raise the temperature of the vacuum chamber to 150°C, set the Ar gas flow rate to 50sccm, and the sputtering bias voltage to -40V, and pre-sputter with a DC power supply for 10 minutes to remove oxides or other impurities on the target surface. After the sputtering voltage stabilizes (indicating that the impurities on the target surface have been cleaned up), open the baffle and perform magnetron sputtering.
[0041] Step 5, magnetron sputtering: adjust the sputtering power, Zr 75 Cu 25The sputtering power of the target was set to 150 W, the sputtering power of the Nb target was adjusted to control the Nb content of the amorphous film, and the sputtering time was 50 min;
[0042] At the same time, a comparative example without Nb target sputtering was prepared.
[0043] Step 6. After the sputtering is completed, close the baffle, sputtering source, vacuum chamber heating device, and airflow in sequence. When the air pressure in the vacuum chamber returns to atmospheric pressure, open the chamber door and take out the sample for corrosion resistance test. In order to avoid contaminating the film, wear clean gloves during the sampling process.
[0044] The structure, morphology and electrochemical properties of the amorphous alloy film prepared in this embodiment were tested, and the specific testing method is as follows:
[0045] In this embodiment, three Zr-based amorphous films modified with different Nb contents were prepared by dual-target sputtering method, which were named Nb1, Nb2 and Nb3 respectively. The contents of all elements in ZrCu, Nb1, Nb2 and Nb3 were detected using a scanning electron microscope (FESEM, FEI Nova Nano SEM430). The detection results are shown in Table 1.
[0046] Table 1 Element distribution and sputtering power in ZrCu, Nb, Nb2 and Nb3
[0047]
[0048] The test results in Table 1 show that with the increase of sputtering power on the Nb target, the contents of Nb and ZrCu increase and decrease, respectively.
[0049] The electrochemical corrosion performance of amorphous alloy film samples was tested using the CorrTest electrochemical test system (see the literature "Evolution in microstructure, wear, corrosion, and tribocorrosion behavior of Mo-containing high-entropy alloy coatings fabricated by laser cladding"). Figure 1 The polarization curves of Zr-based coatings with different Nb contents in 3.5wt.% sodium chloride solution are shown in Figure 2. The results show that each group of films has a passivation zone, a transition zone and an activation zone, which indicates that each group of films has effective passivation in sodium chloride solution. Since the parameters Ecorr and Epit are the corrosion potential and breakdown potential, respectively, their difference (E corr -E pit) is used to determine the size of the passivation zone, where a larger passivation zone has a stronger resistance to pitting corrosion on the metal passivation film. It can be clearly seen that the passivation range of the Nb2 sample is larger and it can more effectively resist the corrosion environment in the simulated marine environment.
[0050] The electrochemical parameters of Nb1, Nb2, and Nb3 metal coatings are shown in Table 2.
[0051] Table 2 Electrochemical parameters of Zr-based amorphous films with different Nb contents
[0052]
[0053] The test results in Table 2 show that all samples have good comprehensive corrosion resistance in 3.5wt.% sodium chloride solution. However, with the increase of Nb concentration, the corrosion potential of the alloy gradually increases, the polarization current gradually decreases, and the passivation zone expands significantly. The Nb2 curve shows that the ΔEp value is 255mV, which exceeds the performance of other films with different compositions and is the maximum passivation interval for preventing corrosion. According to the laws of thermodynamics, during the corrosion process, the Nb2 curve indicates that the corrosion potential is the highest and the corrosion current is small, which significantly slows down the corrosion rate and inhibits the occurrence of pitting corrosion. Therefore, the Zr represented by the Nb2 sample 72.3 Cu 18.2 Nb 9.5 The components are considered to be the optimal ingredients.
[0054] After confirming that the amorphous film prepared in this embodiment has high physical and chemical properties, the EDS method is used to determine that the composition of the Nb1, Nb2, and Nb3 films is Zr 75.2 Cu 17.7 Nb 7.7 、Zr 72.3 Cu 18.2 Nb 9.5 and Zr 68.6 Cu 20 Nb 11.4 , Zr, Cu, and Nb elements are evenly distributed without aggregation. The EDS test results of Nb2 thin film are as follows Figure 2 shown. Figure 2 In the figure, (a) is the atomic energy spectrum of Nb2 film, (b) is the distribution of three elements in the film, and (c)-(e) are the distribution of Zr, Cu, and Nb in Nb2 film. Generally speaking, structural defects on the surface of the film will affect the stability and solubility of the passivation film, among which physical damage or inhomogeneity changes the corrosion resistance of the film.
[0055] The structure of the Nb2 amorphous alloy film was tested by GIXRD (for the test method, see the literature "Liang Wangsheng, Tao Ye, Liu Hongliang. Study on the microstructure of the ion-implanted layer of TiAlN film by synchrotron radiation grazing incidence X-ray diffraction [J]. Physical Testing, 2011, 29(02): 5-9. DOI: 10.13228 / j.boyuan.issn1001-0777.2011.02.013."). The test results are as follows: Figure 3 As shown in the figure, at an incident angle of 4, a broad peak with very high intensity centered at 2θ=35° and another broad peak with relatively small diffraction intensity centered at 2θ=61° were observed. Obviously, these diffraction patterns show the characteristics of glass structure, and no obvious crystal peaks appear within the sensitivity limit of GIXRD measurement, which fully demonstrates the amorphous state of the Nb2 film prepared by a single target. It can be seen that the addition of 9.5% Nb does not introduce a new crystalline phase, but retains the amorphous properties of the ZrCu system, thereby successfully preparing the ZrCuNb amorphous alloy film (ZrCuNb TFMG).
[0056] The CorrTest electrochemical test system was used again to test the electrochemical corrosion performance of the amorphous alloy film samples. 72.3 Cu 18.2 Nb 9.5 ) The potential kinetic polarization curve of the amorphous film sample in 3.5wt.% sodium chloride solution is shown in Figure 4 By evaluating the self-corrosion current effect, the uncoated 304ss substrate and Nb2(Zr 72.3 Cu 18.2 Nb 9.5 ) The self-corrosion current density of the coating samples is 0.360μA / cm 2 and 0.015μA / cm 2 . This difference indicates that the self-corrosion current density of the Zr-based amorphous film coated on 304SS is increased by an order of magnitude, indicating its superior corrosion resistance according to the electrochemical corrosion theory. Secondly, the corrosion potential of the 304SS substrate and the coated Nb2 film sample are -283mV and -365mV, respectively, which is very different. The cumulative potential of the composite system 304SS and ZrCuNb TFMG shows a higher negative response relative to the 304 coated 304SS substrate. Therefore, according to the electrochemical corrosion theory, the film layer will preferentially react with the depolarizer in the corrosive electrolyte solution, thereby forcing the protection of the 304SS substrate.
[0057] Figure 5 For uncoated 304ss substrate and Nb2(Zr 72.3 Cu 18.2 Nb 9.5) SEM images of the coated samples after electrochemical corrosion test. Among them, (a) is the uncoated 304ss substrate. It can be seen that after the electrochemical corrosion test, the surface of the 304ss substrate has obvious pitting characteristics, which extend to its depth direction. The coated samples show completely different corrosion characteristics, such as Figure 5 As shown in (b), the film is corroded preferentially, and there is no obvious pitting feature on its 304ss substrate. The film has uniform corrosion and effectively inhibits the occurrence of pitting. This can be attributed to the high negative corrosion potential of the ZrCuNb film relative to the 304ss substrate in 3.5wt.% sodium chloride solution. In addition, the corrosion expansion no longer proceeds along the depth but parallel to the film direction, which means that in 3.5wt.% sodium chloride solution, Nb2(Zr 72.3 Cu 18.2 Nb 9.5 ) The amorphous film and the 304ss matrix form a redox oxidation system, and the film layer is an anode component that promotes the sacrificial cathodic protection of the 304ss matrix by the oxide.
[0058] This embodiment uses Zr 75 Cu 25 Amorphous alloy is used as the matrix material, and on this basis, the content of Nb element is adjusted to optimize the amorphous alloy composition. During the preparation process, an amorphous alloy film with excellent corrosion resistance is successfully prepared by precisely controlling key parameters such as atmosphere conditions, vacuum degree, sputtering temperature, bias voltage and sputtering power. This method provides a comprehensive technical solution to ensure the superior performance of amorphous alloys. In addition, the required raw materials are easily available and the preparation process is simple and feasible. This alloy is suitable for important metal component layers in marine environments, thereby expanding the scope of application of amorphous alloys in industry.
[0059] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A method for preparing a Zr-based amorphous alloy thin film, characterized in that: The specific steps are as follows: 1) Use 304 stainless steel as the substrate and place it above the vacuum chamber of the coating machine. 75 Cu 25 The target and Nb target are fixed under the substrate, respectively, and the chamber is evacuated; 2) Zr 75 Cu 25 The sputtering power of the target material is set to 150W, the sputtering power of the Nb target material is set to 18-30W, and the sputtering is performed for 50 minutes; a Zr-based amorphous alloy film is formed on the surface of the substrate 304 stainless steel.
2. The method for preparing a Zr-based amorphous alloy thin film according to claim 1, characterized in that: The vacuum pumping refers to the chamber vacuum degree of 6×10 -4 Pa.
3. A Zr-based amorphous alloy thin film obtained by the method as described in claim 1 or 2.
4. A Zr-based amorphous alloy thin film material, characterized in that: The chemical formula of this material is Zr 75.2 Cu 17.7 Nb 7.7 、Zr 72.3 Cu 18.2 Nb 9.5 or Zr 68.6 Cu 20 Nb 11.4 .